The Effects of Increased Prosthetic Ankle Motions on the Gait of Persons with Bilateral Transtibial Amputations - Su, Po-Fu (2010)
OBJECTIVE: To determine if the provision of prosthetic ankle motion improves walking performance in persons with bilateral transtibial amputations. DESIGN: Cross-over experimental design in which nineteen persons with bilateral transtibial amputations were fitted with Endolite Multiflex Ankles (flexion unit) and Otto Bock Torsion Adapters (torsion unit) to increase relative motion between the prosthetic foot and socket in the sagittal and transverse planes, respectively. Quantitative gait analyses were performed on subjects as they walked with four prosthetic configurations: baseline without flexion or torsion units, with only the flexion unit, with only the torsion unit, and with both the flexion and torsion units. Data were compared with a control group of fourteen able-bodied subjects. RESULTS: The flexion unit increased ankle sagittal plane motion (6°-7°) and increased positive ankle power (about 0.17 watt/kg). The torsion unit increased transverse plane ankle range of motion by 1°-2°. Responses from questionnaires indicated that 14 of the 19 subjects preferred the prosthetic configuration that included both the flexion and torsion units. Further, the subjects perceived that the increased prosthetic ankle motion was particularly beneficial for improving stability while they walked on uneven terrain. CONCLUSIONS: Both the subjective and objective results suggest that prosthetic foot and ankle components that allow for greater sagittal and transverse plane rotations provide substantial benefit during walking and should be considered for persons with bilateral transtibial amputations. Nonetheless, clinicians should perform individual and appropriate assessments of patients to insure that they capable of using components that may improve mobility while possibly sacrificing some degree of stability.